Urine protein electrophoresis as a prognostic factor in childhood nephrotic syndrome relapse – An observational study in govt. medical college, Mulankunnathukavu, Thrissur (Panacea Journal of Medical Sciences, 2022)
Background: Childhood nephrotic syndrome (NS) is a chronic illness characterized by relapses and remissions. In many there will be disability, caused by the disease and from the treatment in the form of immunosuppression or end stage renal disease. Progression to renal failure will require anticipation for dialysis and/or renal transplant. A noninvasive biomarker such as urine protein profile that accurately predicts responsiveness to steroid therapy would be valuable in predicting the course of nephrotic syndrome. Our study tries to correlate between the selectivity of proteinuria and the outcome of relapses and thus prognosticate the course of the disease. Few similar studies have been done in India.Materials and Methods: Our study is a cross-sectional hospital based study, comprised of a population of 43 children with nephrotic syndrome relapse, between 1 and 14 years of age. Blood and urine samples were collected, to look for selective or nonselective proteinuria using the Agarose gel electrophoresis (Age) method. The treatment for relapse was started with steroid and, outcome was then related to the selectivity of proteinuria.Results: Majority of our patients had non selective proteinuria (NSP) 60.5%, the rest had selective proteinuria (SP) 39.5%.There was a significant relation between nonselective proteinuria and- 1: Hypertension (p =0.049); 2: Low GFR p Conclusion: Non selective proteinuria was more in children, above the age of 6 years (p=0.001).The nonselective proteinuria group took more time for remission pointing to the lesser degree of steroid sensitivity.Non selective proteinuria can be used as a biomarker to predict the course in childhood nephrotic syndrome. The higher prevalence of non-selective proteinuria could be due to severe forms of nephrotic syndrome in our study. Selective proteinuria had a better outcome.